Blue light-emmiting material having a perovskite-like structure and improved photoluminescent quantum yield, and method of preparing same
Patent Information
- Application Number
- KR1020230190429
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-22
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2043-12-22
Smart Images

Figure 112023144902650-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a blue light-emitting material having a perovskite-like structure and exhibiting excellent luminescence efficiency, and a method for manufacturing the same. Background Technology
[0002] Blue phosphor materials used in LEDs and the like require physical properties such as high color purity and / or thermal stability. Examples of currently known blue phosphor materials include CaWO4 phosphors emitting wavelengths of approximately 400 nm to 420 nm and MgWO4 phosphors emitting wavelengths around 480 nm, with lead (Pb) used as an activator. In the case of these phosphors, light is emitted from the activator doped into the host, resulting in a broad fluorescence spectrum (i.e., low color purity), and there is a problem regarding the inclusion of lead (Pb), which is harmful to the human body. Another example of a blue phosphor composition is Eu 2+ BaMaAl using ions as activators 10 O 17 :Eu 2+ Although there are light-emitting materials, they also tend to contain a large amount of light in the green region, resulting in low color purity and low thermal stability, which limits the lifespan of the phosphor.
[0003] Meanwhile, compounds having a perovskite structure with the formula AMX3 (A is a cation, M is a metal cation, and X is an anion) are used in various fields such as displays, light-emitting diodes, solar cells, photodetectors, and lasers due to their high quantum yield, large absorption coefficient, and tunable bandgap characteristics. Although perovskite structures exhibit excellent optical properties including high luminescence efficiency, there is a need to overcome their harmfulness as they contain divalent cations such as Pb and Sb as metal cations. The problem to be solved
[0004] One embodiment provides a new blue light-emitting material that has high color purity, excellent thermal stability, and excellent luminous efficiency.
[0005] Another embodiment provides a method for manufacturing the new blue light-emitting material. means of solving the problem
[0006] A blue emitting material according to one embodiment is represented by the following chemical formula 1, is excited by an excitation source in the wavelength range of 250 nm to 400 nm, has an emission peak wavelength in the wavelength range of 380 nm to 500 nm, has a full width at half maximum of the emission spectrum of less than 30 nm, has a photoluminescent quantum yield (PLQY) of 80% or more, and has an average emission lifetime of 80 nanoseconds or more:
[0007] (Chemical Formula 1)
[0008] AMX4
[0009] In the above chemical formula 1,
[0010] A includes Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and
[0011] M includes Sc, Y, Al, Gd, Lu, or a combination thereof, and
[0012] X includes O, F, Cl, Br, I, or a combination thereof.
[0013] In the above chemical formula 1,
[0014] A includes Rb, Cs, Sr, Ba, or a combination thereof, and
[0015] M includes Sc, Y, Al, or a combination thereof, and
[0016] X includes F, Cl, Br, or a combination thereof.
[0017] The above chemical formula 1 can be represented by the following chemical formula 2 or the following chemical formula 3:
[0018] (Chemical Formula 2)
[0019] (A 1-x B x)(M 1-y N y )X4
[0020] (Chemical Formula 3)
[0021] (A 1-2x B x )(M 1-y N y )X4
[0022] In the above chemical formula 2 and the above chemical formula 3,
[0023] A is Rb, and
[0024] B includes Li, Na, K, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and
[0025] M includes Sc,
[0026] N includes Y, Al, Gd, Lu, or a combination thereof, and
[0027] X includes O, F, Cl, Br, I, or a combination thereof, and
[0028] x is 0.01 ≤ x ≤ 0.10 and y is 0.01 ≤ y ≤ 0.10.
[0029] In the above chemical formulas 2 and 3, B includes Cs.
[0030] In the above chemical formulas 2 and 3, X includes one or more of F, O, Cl, Br, and I.
[0031] In the above chemical formulas 2 and 3, X includes F and O.
[0032] The blue light-emitting material represented by the above chemical formula 1 has an orthorhombic structure of Cmcm, and in the X-ray diffraction pattern, the diffraction angle (2θ) of the first intensity peak and the second intensity peak lower than the first intensity peak is located in the range of 20≤2θ≤30.
[0033] In the blue light-emitting material represented by the above chemical formula 1, the first intensity peak in the X-ray diffraction pattern is located in the range of diffraction angle (2θ) 26.2 ≤ 2θ ≤ 28.2, and the second intensity peak is located in the range of diffraction angle (2θ) 25.8 ≤ 2θ ≤ 27.8.
[0034] The blue light-emitting material represented by the above chemical formula 1 is RbScF4.
[0035] A method for manufacturing the blue fluorescent material according to another embodiment is,
[0036] A halide of one or more elements including Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and a halide of one or more elements including Sc, Y, Al, Gd, Lu, or a combination thereof are mixed, and
[0037] The above mixture is heat-treated at a temperature of 500°C or higher and 600°C or lower under a strongly reducing atmosphere, and
[0038] The above heat-treated mixture may be sintered at a temperature greater than 600°C and less than or equal to 700°C under a strongly reducing atmosphere.
[0039] The above-mentioned strong reducing atmosphere includes heat-treating the mixture with magnesium powder, titanium powder, or a combination thereof.
[0040] The above manufacturing method further includes grinding the mixture before the heat treatment.
[0041] The above manufacturing method further includes additionally grinding the mixture after the heat treatment and before the sintering.
[0042] The above manufacturing method further includes additionally grinding the mixture after sintering.
[0043] The above manufacturing method further includes grinding the mixture before the heat treatment, after the heat treatment, and after the sintering, respectively.
[0044] A blue emitting material according to another embodiment is a material represented by the following chemical formula 1, prepared by mixing a halide of one or more elements including Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof with a halide of one or more elements including Sc, Y, Al, Gd, Lu, or a combination thereof, heat-treating the mixture together with magnesium powder, titanium powder, or a combination thereof, and sintering the heat-treated mixture at a temperature higher than the heat-treatment temperature, wherein the material is excited by an excitation source in the wavelength range of 250 nm to 400 nm and has an emission peak wavelength in the wavelength range of 380 nm to 500 nm, has a full width at half maximum of the emission spectrum of less than 30 nm, has a photoluminescent quantum yield (PLQY) of 80% or more, and has an average emission lifetime of 80 nanoseconds or more:
[0045] (Chemical Formula 1)
[0046] AMX4
[0047] In the above chemical formula 1,
[0048] A includes Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and
[0049] M includes Sc, Y, Al, Gd, Lu, or a combination thereof, and
[0050] X includes O, F, Cl, Br, I, or a combination thereof.
[0051] The above blue light-emitting material is RbScF4. Effects of the invention
[0052] A blue light-emitting material according to one embodiment is a lead-free blue light-emitting phosphor, and compared to conventionally known lead-free blue light-emitting phosphors, it has superior quantum efficiency (PLQY), a narrow full width at half maximum of the emission spectrum, excellent thermal and chemical stability, and a long light-emitting lifetime. Therefore, the blue light-emitting material according to one embodiment can be advantageously applied to various light-emitting devices, such as light-emitting diodes (LEDs), solar cells, photovoltaic cells, sensors, and color filters, without environmental issues. Brief explanation of the drawing
[0053] Figure 1 is a graph showing the X-ray diffraction patterns of RbScF4 prepared in a strong reduction condition (SRC), a mild reduction condition (MRC), and an inert condition (IC), respectively. Figure 2 is a graph of the photoluminescence intensity (PL(Photoluminescence) intensity) of RbScF4 prepared under SRC, MRC, and IC conditions. Figure 3 is a graph showing the absorbance and corresponding band gap energy of RbScF4 synthesized in an inert atmosphere (IC) and a strongly reducing atmosphere (SRC), respectively. Figure 4 shows the structural model of RbScF4 used for calculations based on density functional theory (DFT), where (a) shows the RbScF4 unit cell optimized by the PBE (Perdew-Burke-Ernzerhof) functional, and (b) shows the extended 3×1×2 supercell model used for electronic structure calculations. Figure 5 shows the schematic crystal structures of the supercell model (a) of RbScF4 shown in Figure 4 (b), the RbScF4 (RbScF4-1V) model (b) having one F defect in the model (a), and the RbScF4 (RbScF4-2V) model (c) having two F defects in the model (a). Figure 6 shows graphs representing the electronic structures evaluated by the conventional HSE (Heyd-Scuseria-Ernzerhof)06 functional (α=0.25) for each model of Figure 5. Figure 7 is a schematic diagram showing the effect of F defects on the density of states and band gap energy for each model of Figure 5. Figure 8 is a graph showing the change in emission intensity (PL intensity) at a 420 nm emission wavelength of RbScF4 prepared in a strong reducing atmosphere (SRC), a weak reducing atmosphere (MRC), and an inert atmosphere (IC), respectively, monitored over time. Figure 9 is a thermoluminescence (TL) spectral graph of RbScF4 prepared in a strong reducing atmosphere (SRC), a weak reducing atmosphere (MRC), and an inert atmosphere (IC), respectively, as a function of temperature. Specific details for implementing the invention
[0054] Lead-free perovskite materials have been known to possess low quantum efficiency (PLQY) due to their low absorption coefficients. Furthermore, device characteristics using lead-free perovskite materials are significantly lower than those of lead-based materials. The performance, stability, and efficiency of lead-free perovskite materials remain lower than those of lead-based perovskite materials due to their low PLQY values. Therefore, there is a need to improve the quantum efficiency of lead-free perovskite materials.
[0055] Recent studies on lead-free perovskite materials, e.g., Cs3CuI5, (C9NH 20)2SnBr4, etc., compared to lead-based perovskites, e.g., CsPbX3, exhibit superior luminescence characteristics, e.g., high quantum efficiencies (PLQY) of 90% and 46%, respectively, and high exciton binding energies (E b It has been reported to have ). However, Sn in air 2+ or Cu + The oxidation of ions and the instability of organic components against moisture and heat impose limitations on the practical application of these materials, leaving issues that still need to be addressed.
[0056] The inventors of the present invention have completed the present invention by developing a novel blue emitting material as a lead-free layered perovskite-like material, which is excited by an excitation source in the wavelength range of 250 nm to 400 nm and has an emission peak wavelength in the wavelength range of 380 nm to 500 nm, has a full width at half maximum of less than 30 nm, a quantum efficiency of 80% or more, and an average emission lifetime of 80 nanoseconds or more. The blue emitting material can be represented by the following chemical formula 1:
[0057] (Chemical Formula 1)
[0058] AMX4
[0059] In the above chemical formula 1,
[0060] A includes Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and
[0061] M includes Sc, Y, Al, Gd, Lu, or a combination thereof, and
[0062] X includes O, F, Cl, Br, I, or a combination thereof.
[0063] In the above chemical formula 1, A may include Rb, Cs, Sr, Ba, or a combination thereof, M may include Sc, Y, Al, or a combination thereof, and X may include F, Cl, Br, or a combination thereof.
[0064] The substance represented by the above chemical formula 1 can be represented by the following chemical formula 2 or the following chemical formula 3:
[0065] (Chemical Formula 2)
[0066] (A 1-x B x )(M 1-y N y )X4
[0067] (Chemical Formula 3)
[0068] (A 1-2x B x )(M 1-y N y )X4
[0069] In the above chemical formula 2 and the above chemical formula 3,
[0070] A is Rb, and
[0071] B includes Li, Na, K, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and
[0072] M includes Sc,
[0073] N includes Y, Al, Gd, Lu, or a combination thereof, and
[0074] X includes O, F, Cl, Br, I, or a combination thereof, and
[0075] x can be 0.01 ≤ x ≤ 0.10 and y can be 0.01 ≤ y ≤ 0.10.
[0076] In the above chemical formulas 2 and 3, B may include Cs, and X may include one or more of F, and O, Cl, Br, and I, for example, X may include F and O.
[0077] The blue emitting material represented by the above chemical formula 1 has an orthorhombic structure of Cmcm, and as can be seen from the X-ray diffraction pattern of FIG. 1, the diffraction angle (2θ) of the first intensity peak and the second intensity peak lower than the first intensity peak may be located in the range of 20≤2θ≤30. For example, in the X-ray diffraction pattern of the blue emitting material represented by the above chemical formula 1, the first intensity peak may be located in the range of diffraction angle (2θ) of 26.2≤2θ≤28.2, and the second intensity peak may be located in the range of diffraction angle (2θ) of 25.8≤2θ≤27.8.
[0078] As can be seen from FIG. 1, the X-ray diffraction pattern of the blue emitting material represented by Chemical Formula 1 shows that, as long as the types of A, M, and X in Chemical Formula 1 are the same, the diffraction angle (2θ) pattern is basically the same even if synthesized under different reduction conditions. That is, even if synthesized under different reduction conditions, as long as the types of A, M, and X are the same, the basic crystal structure of the blue emitting material represented by Chemical Formula 1 is the same.
[0079] However, as can be seen from FIG. 2, the luminescence intensity of the blue light-emitting material represented by Chemical Formula 1 varies depending on the reduction conditions. That is, when synthesized in an inert atmosphere (IC: Inert Condition) such as Ar gas, the manufactured material exhibits almost no luminescence or only very low luminescence. However, when manufactured in a mild (or weak) reducing gas atmosphere (MRC: Mild Reduction Condition) mixed with hydrogen and nitrogen, it becomes a material that exhibits low luminescence intensity. Furthermore, it can be confirmed that when manufactured in a stronger reducing atmosphere (SRC: Strong Reduction Condition), the material represented by Chemical Formula 1 exhibits strong luminescence intensity. In other words, the inventors of the present invention completed the present invention by discovering that the material represented by Chemical Formula 1, which exhibited very low luminescence characteristics when manufactured in an inert atmosphere, exhibits high luminescence characteristics when manufactured in a reducing atmosphere, and furthermore, can be manufactured into a blue light-emitting material that exhibits even stronger luminescence characteristics when manufactured in a strong reducing atmosphere (SRC).
[0080] In this regard, the inventors of the present invention have manufactured a blue emitting material having a quantum efficiency (PQLY) of approximately 80% in Korean Patent Application No. 2020-0177270 (filed Dec. 17, 2020; Korean Patent Application Publication No. 2022-0086985A1; published June 24, 2022) by manufacturing a material represented by Chemical Formula 1 without applying a reducing atmosphere in the first heat treatment step, and by manufacturing it in a weak reducing atmosphere (MRC) using a mixed gas of hydrogen and nitrogen in the second sintering step. The entirety of the said patent application is incorporated by reference into the specification of this application. The said patent application manufactured a blue emitting material exhibiting luminescence characteristics similar to those of the present invention by sintering the final material using a mixed gas containing hydrogen gas in an amount of approximately 5% to 30%. However, as described below, the present invention was able to obtain a new blue light-emitting material with much stronger luminescence characteristics and a longer luminescence lifetime than the blue light-emitting material disclosed in Korean Patent Application No. 2020-0177270 by heat-treating under a strong reducing atmosphere (SRC) not only in the final sintering step but also in the heat treatment step prior thereto, and sintering under a strong reducing atmosphere (SRC) in the subsequent sintering step. The fact that the luminescence characteristics of the material represented by Chemical Formula 1 can be controlled by controlling the reducing atmosphere is a surprising result that could not have been anticipated from Korean Patent Application No. 2020-0177270.
[0081] In one embodiment, the blue emitting material represented by Chemical Formula 1 may be RbScF4. RbScF4 as prepared in the following examples has an emission peak wavelength of about 420 nm, a PLQY of 80% or more, a full width at half maximum (FWHM) of about 25 nm, and an average luminescence lifetime of 80 ns or more, possessing high stability and excellent luminescence characteristics. The blue emitting material represented by Chemical Formula 1 prepared in the above Korean patent application, e.g., RbScF4, has a PLQY similar to the material represented by Chemical Formula 1 of the present invention, but has a lower luminescence lifetime and, as shown in FIG. 2, a much lower luminescence intensity (PL intensity). Therefore, the blue emitting material represented by Chemical Formula 1 according to the present invention is a material different from the blue emitting material disclosed in the above Korean patent application No. 2020-0177270, and can be recognized as a novel and improved material in itself.
[0082] Here, "luminescence lifetime" refers to the time spent in the excited state from the moment a luminescent material is excited until it emits a photon and returns to the ground state. The luminescence lifetime of a photon exhibits an exponentially decreasing distribution due to energy loss caused by luminescence or non-luminescence, and the time until it reaches approximately 36.8% of the initial luminescence intensity is defined as the average luminescence lifetime. The luminescence lifetime can be measured by irradiating the luminescent material with a short-wavelength pulsed laser as the excitation source using a time-resolved fluorescence spectrometer.
[0083] To elucidate the luminescence mechanism of a blue luminescent material according to one embodiment, the inventors of the present invention performed calculations based on density functional theory (DFT). Generally, defect-assisted luminescence materials exhibit a broad emission band. Accordingly, the blue luminescent material according to one embodiment also obtained a very wide bandgap value exceeding 8.0 eV from the DFT calculation results. However, the RbScF4 actually manufactured according to one embodiment has a very narrow full width at half maximum (FWHM) of about 25 nm and exhibits high PLQY, which is a very unusual optical property among existing luminescent materials. Surprisingly, the RbScF4 according to one embodiment exhibits a narrow emission band due to defects within the crystal structure in the blue light region in the bulk state, which confirmed that F defects in RbScF4 form defect levels within the RbScF4 band, thereby becoming an important factor in blue luminescence. In addition, as can be seen from Figures 5 and 6, it was confirmed that the width (ΔE) of the defect level and the band gap energy change depending on the F defect concentration within the crystal structure of the material. That is, the sharp and localized lower defect level (LDL) and upper defect level (UDL) of RbScF4 provide a theoretical explanation for the experimentally observed narrow full width at half maximum of RbScF4. Although we do not wish to be bound by a specific theory, it is thought that the pair of localized defect levels participate in the photoluminescence sequence, narrowing the full width at half maximum of the blue-emitting material and increasing PLQY.
[0084] Specifically, the fluorine (F) defects introduced into RbScF4 are at the Fermi level (E F It generates pairs of sharply localized defect levels higher than ). Interestingly, secondary fluoride defects rearrange defect levels, causing LDL to rise to the Fermi level (E FIt is positioned close to the conduction band edge, and the UDL is placed just below the conduction band edge. Accordingly, the energy gap between the occupied LDL and the empty UDL becomes 2.20 eV, which is lower than the experimental value of 3.05 eV. This is an unusual phenomenon that has not been observed in existing libraries of luminescent materials. Furthermore, the blue luminescent material according to one embodiment may improve the PLQY value by increasing the defect concentration by changing atmospheric conditions.
[0085] Meanwhile, according to one embodiment, the blue fluorescent material can be manufactured by mixing a halide of one or more elements including Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof with a halide of one or more elements including Sc, Y, Al, Gd, Lu, or a combination thereof, heat-treating the mixture for a certain period of time at a temperature of 500°C or higher and 600°C or lower under a strong reducing atmosphere (SRC), and sintering the heat-treated mixture again at a temperature of 600°C or higher and 700°C or lower under a strong reducing atmosphere. The strong reducing atmosphere (SRC) includes heat-treating the mixture together with magnesium powder, titanium powder, or a combination thereof, and the same strong reducing atmosphere is applied during the sintering process after the heat treatment.
[0086] As described above, the blue light-emitting material according to one embodiment can exhibit excellent light-emitting properties as described above by being manufactured under a strongly reducing atmosphere (SRC). In particular, the blue light-emitting material can be manufactured through a solid-state synthesis method. Here, the solid-state synthesis method means mixing and reacting precursor materials in stoichiometric amounts to produce the material represented by Chemical Formula 1, wherein such reaction takes place in a solid state rather than in a solution state. Specifically, the precursor materials are weighed in stoichiometric amounts and mixed in a solid state, either without any solvent or by adding only a small amount of liquid medium for uniform mixing, and then the solvent used for mixing is removed, followed by heat treatment and sintering to produce the material.
[0087] As a solvent that can be used for the above mixing, acetone, alcohol, distilled water, or a mixture thereof may be used, and as an example, acetone may be used. The mixture containing the solvent may be placed in a mixer, such as a ball mill or an agate mortar, and mixed uniformly, after which the solvent may be removed and heat-treated and sintered. The solvent may be mixed in a range of about 100 parts by weight to about 400 parts by weight per 100 parts by weight of the mixture, but is not limited thereto. If the amount of the solvent is less than 100 parts by weight, uniform mixing may be difficult, and if the amount of the solvent exceeds 400 parts by weight, it may take too long to remove the solvent after mixing.
[0088] After the above mixing is completed, the solvent is removed by evaporation, the dried mixture is ground using an agate mortar and pestle, etc., and then heat-treated at a high temperature in a strongly reducing atmosphere. The strongly reducing atmosphere can be formed by placing the mixture in an alumina crucible, etc., and heating it together with metal powders such as magnesium powder and titanium powder in a muffle furnace, etc., when heat-treating the mixture in a muffle furnace, etc. The heat treatment temperature may include heating at a temperature of 500°C or higher and 600°C or lower for about 4 hours to about 6 hours, for example, about 5 hours.
[0089] After the above heat treatment is finished, the mixture is naturally cooled and then ground once again using an agate mortar and pestle. The ground mixture is then placed in a tubular furnace and sintered again in a strongly reducing atmosphere at a temperature higher than the heat treatment temperature, for example, at a temperature of 600°C or higher and 700°C or lower, for about 5 hours to about 7 hours, for example, about 6 hours. After the sintering is finished, the mixture is cooled and then ground again using an agate mortar and pestle, thereby producing a blue light-emitting material according to one embodiment.
[0090] In the blue light-emitting material according to one embodiment manufactured in this manner, a defect is formed in which an element represented by X, such as fluorine (F), escapes from the layered structure of the material represented by Chemical Formula 1 due to the strong reducing atmosphere described above. Unlike a material that does not contain such defects, the material represented by Chemical Formula 1 manufactured including such defects can exhibit excellent blue light-emitting characteristics. As can be seen from the examples described below, by controlling the strong reducing atmosphere, the light-emitting characteristics of the manufactured blue light-emitting material, such as light intensity and light-emitting lifespan, can be controlled.
[0091] Meanwhile, the aforementioned heat treatment temperature and / or time may affect the crystal structure, crystal size, crystallinity, or luminous efficiency of the blue light-emitting material being manufactured. For example, if the heat treatment temperature is 500 ℃ or lower, it is difficult to form crystals, and if the heat treatment temperature is too high (e.g., exceeding 700 ℃), it may be difficult to form crystals from the reactants, or the crystallinity of the formed crystallinity may decrease, or the aggregation of crystals may occur, which may lead to a decrease in the manufacturing yield and luminous efficiency of the light-emitting material. Therefore, the aforementioned heat treatment and sintering temperatures can be performed at appropriate temperatures and times.
[0093] The present invention will be described in detail below according to the embodiments. However, these embodiments are merely for illustrating the present invention and are not intended to limit the scope of the present invention, and the scope of the present invention may be defined by the claims attached to this specification.
[0095] Examples
[0096] Synthesis Example: Blue light-emitting material RbScF 4 Synthesis of
[0097] As commercially available starting materials, RbF (Sigma-Aldrich, 99.9%) and ScF3 (Kojundo, 99.9%) were used without further purification. RbScF4, a lead-free layered perovskite analog, was synthesized through the following process.
[0098] Specifically, the two starting materials are stoichiometrically weighed and then uniformly mixed with a small amount of acetone in an agate motor for about 30 minutes and dried. For example, about 0.25004 g (1 mol) of RbF and about 1 g of ScF3 are used per mole of RbScF41. The powder obtained as described above is placed in an alumina crucible and heat-treated at a temperature of about 550°C for about 5 hours in a muffle furnace containing titanium powder and magnesium powder. At this time, the amounts of titanium powder and magnesium powder used are 1 g each per mole of RbScF41. After the heat treatment, the obtained powder is ground using an agate motor, placed in a tubular furnace, and sintered by heating at a temperature of about 650°C for about 6 hours in the muffle furnace containing titanium powder and magnesium powder. After sintering is finished, the obtained powder is cooled to room temperature and then processed again using an agate mortar to produce a fine powder with a particle size of about 30 to 50 micrometers. The blue light-emitting particles produced in this way are named as the blue light-emitting material according to the example prepared in a strong reducing atmosphere (SRC).
[0099] Meanwhile, a blue emitting material is manufactured in the same manner as described above, but in the heat treatment and sintering steps, a material manufactured in an inert atmosphere (IC) using argon gas without using a reducing atmosphere is designated as a control material.
[0100] In addition, a blue light-emitting material is manufactured in the same manner as described above, but in the heat treatment and sintering steps, the blue light-emitting material manufactured in a weak reducing atmosphere (MRC) in which the hydrogen gas content is 25% of a mixture of hydrogen and nitrogen gases as the reducing atmosphere is named as the blue light-emitting material according to the comparative example.
[0102] evaluation
[0103] (1) X-ray diffraction pattern measurement, and emission intensity measurement
[0104] The X-ray diffraction patterns and luminescence intensities of each blue light-emitting material according to the above examples, control group, and comparative example were measured and are shown in FIGS. 1 and FIGS. 2.
[0105] From FIG. 1, it can be seen that the X-ray diffraction patterns of each material according to the control group (IC), comparative example (SRC), and example (SRC) are all identical. That is, even if different atmospheric conditions are applied during the heat treatment and sintering processes, such atmospheric conditions do not alter the crystal structure of the material, and the original crystal structure is maintained even when the atmospheric conditions change.
[0106] On the other hand, from FIG. 2, it can be seen that the atmospheric conditions during the heat treatment and sintering processes changed the luminescence characteristics of each material. Specifically, the control material prepared in an inert atmosphere (IC) showed almost no luminescence characteristics, whereas the material according to the comparative example, to which a weak reducing atmosphere (MRC) with a hydrogen gas content of 25% was applied, showed luminescence characteristics, although lower than those of the example material. In the case of the example, using a strong reducing atmosphere (SRC) resulted in a luminescence intensity approximately four times higher than that of the comparative example. That is, it can be confirmed that although the crystal structure is not altered by atmospheric conditions, the luminescence characteristics of the material changed by controlling the concentration of defects (or traps) within the crystal structure.
[0107] (2) Measurement of changes in light absorption characteristics and energy bandgap
[0108] From the results of Figure 2 above, the light absorption characteristics of the control material prepared in an inert atmosphere (IC) and the material according to the example prepared in a strong reducing atmosphere (SRC) were measured, and the energy band gaps were measured accordingly and shown in Figure 3.
[0109] As shown in Figure 3, the control RbScF4 prepared in an inert atmosphere (IC) exhibits a very high bandgap energy of 7.2 eV, which cannot explain the blue luminescence observed at approximately 420 nm. On the other hand, the example RbScF4 prepared in a strongly reducing atmosphere (SRC) exhibits a significantly reduced bandgap energy of 2.92 eV, which exactly matches the energy associated with the blue luminescence. Consequently, the energy change according to the defect state of each material can be confirmed from the experimentally observed bandgap energy.
[0110] (3) Analysis of changes in luminescence characteristics due to F defects caused by reducing atmosphere control
[0111] As can be seen from FIGS. 1 and 2, the materials according to the control group, comparative example, and example do not show a change in X-ray diffraction pattern, but their luminescence intensities differ from one another. From this, it can be seen that the increase in luminescence intensity of the blue luminescent material according to the present invention is due to a change in a specific element within the material caused by the control of the reducing atmosphere.
[0112] Accordingly, to explain the factors that caused the change in luminescence intensity, calculations were performed based on density functional theory (DFT). Figure 4 shows the structural model of RbScF4 used for density functional theory calculations, where (a) represents an RbScF4 unit cell optimized by the PBE (Perdew-Burke-Ernzerhof) functional, and (b) represents an extended 3×1×2 supercell model used for electronic structure calculations.
[0113] In addition, FIG. 5 shows the schematic crystal structures of the supercell model (a) of RbScF4 shown in FIG. 4(b), the RbScF4 (RbScF4-1V) model (b) having one F defect within model (a), and the RbScF4 (RbScF4-2V) model (c) having two F defects within model (a). All models were initially optimized using the PBE function and used for additional electronic structure calculations. The most stable defect location was identified by comparing the total energies of supercells having F defects at various locations.
[0114] Figure 6 shows graphs representing the electronic structures evaluated by the conventional HSE (Heyd-Scuseria-Ernzerhof)06 functional (α=0.25) for each model of Figure 5.
[0115] Figure 7 is a schematic diagram showing the effect of F defects on the density of states and band gap energy for each model of Figure 5.
[0116] The electronic structure and density of states (DOS) of RbScF4 were simulated based on spin-polarized density functional theory (DFT) calculations. Rb is shown in Figures 4a and 4b. 24 Sc 24 F 96 The electronic structure and density of RbScF4 were defined based on 2x1x2 and 3x1x2 slab models. Based on simulation results, the bandgap energy of defect-free RbScF4 is estimated to be greater than 10 eV (see Figs. 5a and 6a). The charge at the conduction band (CB) edge is mainly formed by Sc(d) orbitals, while the charge at the valence band (VB) edge is mainly generated in F(p) orbitals. However, these results do not explain the origin of the blue emission of RbScF4's wide bandgap energy, which reaches 10 eV.
[0117] As shown in FIG. 5b, F vacancy defects were created within RbScF4, and FIG. 6b and FIG. 7b respectively simulated and illustrated the band structure and DOS of the RbScF4 with the created F vacancy. As seen in FIG. 6b and FIG. 7b, after the introduction of F vacancy into RbScF4, the Fermi level (E F It can be seen that the defect pair above is generated. Additionally, as the F void is additionally introduced in Fig. 5c, the defect levels are rearranged as in Figs. 6c and 7c, so that the low defect level (LDL) is exactly E F As a result, it can be seen that the upper defect level (UDL) is shifted just below the conduction band edge.
[0118] In addition, the gap between the occupied LDL and the empty UDL in Figs. 6c and 7c is 2.92 eV, which is nearly identical to the experimental bandgap energy value of 2.95 eV of RbScF4 fabricated in the SRC of Fig. 3. That is, the energy difference between the corresponding defect states matches the blue luminescence energy of RbScF4, thus supporting the idea that the sharp and localized LDL and UDL in Fig. 7c are the source of the blue luminescence.
[0119] (4) Average luminescence lifetime measurement evaluation
[0120] Figure 8 is a graph monitoring the change in luminescence intensity (PL intensity) at a 420 nm emission wavelength of RbScF4 prepared in the example, comparative example, and control group, respectively, over time. From this graph, the average luminescence lifetime of the materials prepared under different atmospheric conditions can be compared. Since the photoluminescence lifetime of a material is proportional to its luminescence efficiency, the graph in Figure 8 supports the increase in luminescence efficiency of the materials prepared under each synthesis atmosphere.
[0121] From FIG. 8, it can be seen that the average luminescence lifetime of the RbScF4 according to the example prepared in a strong reducing atmosphere (SRC) is further extended compared to the RbScF4 according to the comparative example prepared in a weak reducing atmosphere (MRC).
[0122] (5) Evaluation of Thermal Luminescence (TL) Intensity
[0123] Figure 9 is a thermoluminescence (TL) spectral graph for RbScF4 prepared in a strong reducing atmosphere (SRC), a weak reducing atmosphere (MRC), and an inert atmosphere (IC), respectively.
[0124] As shown in Figure 9, RbScF4 prepared in SRC and MRC, respectively, exhibit two distinct peaks within each graph. These peaks represent the level of F defects within the layered structure of each material, and by comparing the regions of each peak, it can be confirmed that the RbScF4 prepared in SRC has the highest trap density. Additionally, the RbScF4 prepared in IC exhibits very low peaks, indicating that almost no F defects occurred within the layered structure.
[0125] From these TL intensity evaluation results, the correlation between the luminescence characteristics due to defects in RbScF4 produced according to each atmospheric condition can also be supported.
[0127] Although the present invention has been described illustratively according to embodiments, the scope of the present invention is not limited thereby, and those skilled in the art will understand that various modifications and variations are possible within the scope of the essential characteristics of the present invention. Accordingly, the embodiments described above may be implemented separately or in combination, and the scope of protection of the present invention should be interpreted by the claims below, and all technical concepts within the equivalent scope should be interpreted as being included within the scope of rights of the present invention.
Claims
Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 A method for manufacturing a blue emitting material, comprising mixing a halide of one or more elements including Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, and a halide of one or more elements including Sc, Y, Al, Gd, Lu, or a combination thereof, heat-treating the mixture together with magnesium powder, titanium powder, or a combination thereof at a temperature of 500°C or higher and 600°C or lower, and sintering the heat-treated mixture together with magnesium powder, titanium powder, or a combination thereof at a temperature of 600°C or higher and 700°C or lower. Claim 11 A method for manufacturing a blue emitting material according to claim 10, wherein the heat treatment and sintering of the mixture are each performed together with magnesium powder. Claim 12 A method for manufacturing a blue emitting material according to claim 10, wherein the manufacturing method further comprises grinding the mixture before the heat treatment. Claim 13 A method for manufacturing a blue light-emitting material according to claim 10, wherein the manufacturing method further comprises additionally grinding the mixture after the heat treatment and before the sintering. Claim 14 A method for manufacturing a blue light-emitting material according to claim 10, wherein the manufacturing method further comprises grinding the mixture after sintering. Claim 15 A method for manufacturing a blue light-emitting material according to claim 10, wherein the manufacturing method further comprises grinding the mixture before the heat treatment, after the heat treatment, and after the sintering, respectively. Claim 16 In claim 10, the method for manufacturing the blue emitting material is a method for manufacturing a material represented by the following chemical formula 1: (Chemical Formula 1) AMX4, wherein A comprises Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, or a combination thereof, M comprises Sc, Y, Al, Gd, Lu, or a combination thereof, and X comprises O, F, Cl, Br, I, or a combination thereof. Claim 17 A method for manufacturing a blue emitting material according to claim 16, wherein the substance represented by the above chemical formula 1 is RbScF4.
Citation Information
Patent Citations
Phosphor, method for producing same, phosphor-containing composition, light-emitting device, image display, and illuminating device
KR1020080091295A
Blue light-emmiting compounds wiht a perovskite-like structure and method of manufacturing the same
KR1020220086985A
